2013
DOI: 10.1097/iae.0b013e318263d11f
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal Thickness in Central Serous Chorioretinopathy

Abstract: The choroid is diffusely thickened in CSC likely because of the choroidal vascular dilatation. The nasal macula undergoes the greatest alterations in choroidal thickness compared with the other areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
112
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(120 citation statements)
references
References 17 publications
(28 reference statements)
7
112
0
1
Order By: Relevance
“…In addition, this finding implies a correlation between the occurrence of CSC in pregnant women and increased CT in pre-eclamptic patients, because increased choroidal hydrostatic pressure contributes to CSC occurrence, and choroidal delayed filling in CSC was reported previously. 6,10,23 In this study, a small amount of subretinal fluid was seen in one patient with pre-eclampsia, but it was absorbed after delivery. Note that the systemic hypertension in this patient was controlled 5 days before the ophthalmic examination, and the CT decreased with the disappearance of the subretinal fluid ( Figure 2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, this finding implies a correlation between the occurrence of CSC in pregnant women and increased CT in pre-eclamptic patients, because increased choroidal hydrostatic pressure contributes to CSC occurrence, and choroidal delayed filling in CSC was reported previously. 6,10,23 In this study, a small amount of subretinal fluid was seen in one patient with pre-eclampsia, but it was absorbed after delivery. Note that the systemic hypertension in this patient was controlled 5 days before the ophthalmic examination, and the CT decreased with the disappearance of the subretinal fluid ( Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] Choroidal thickening was observed in eyes with CSC or polypoidal choroidal vasculopathy and choroidal atrophy was also noted in eyes with age-related macular degeneration. 6,12,13 An association between choroidal thickening and choroidal vascular hyperpermeability was reported in previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subfoveal CT is reported to increase in some diseases, such as polypoidal choroidal vasculopathy (11) and central serous chorioretinopathy (22), yet in contrast is reported to decrease in retinal angiomatous proliferation (23). If a physician thinks that a patient may have such a disease, extra care must be taken while evaluating the patient's CT.…”
Section: Discussionmentioning
confidence: 99%
“…The study reported new leakages sites in normal eye of CSCR patients when follow up was done for 2 years [7]. Reports [6,19] on Indocyanine green angiography (ICGA) in CSCR revealed instability of choroidal circulation. These studies suggested that increase in choroidal vascular hyperpermeability might be the root cause of CSCR.…”
Section: Discussionmentioning
confidence: 99%